تقييم شرعية النوافذ الإسلامية في مصرف الجمهورية الليبي - مشرقي، رمزي خليفة عمار (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2018)
The overriding purpose of this study is to determine the legitimacy of Islamic windows through the viewpoint of employees and customers at Jumhouria Bank، Libya. The study aims at introducing Islamic windows and knowing the nature of the work of the Shariah Committee in the Islamic windows at this Libyan Bank. It also aims at clarifying the subordination of the internal auditor of the Islamic windows at the legitimate authority that works on these windows; the suitability of the conventional accounting system with the requirements of Islamic banking. The sample for this study included 473 employees and 493 customers. The study adopted the analytical descriptive method through the questionnaire used to collect information about the phenomenon under study. The study reached several results، the most important of which is: the non-independence of the Shariah board for these windows which led to the absence of a special department for the legitimate observers. It also revealed that the reports are referred to the manager of the Islamic banking project instead of the Shariah board. Most customers do not trust dealing with a bank that offers dual financial services. Based on the results of this research، the following recommendation can be made are: the need for independence of the Shari'a Board; preparation of a contract with the General Assembly to clarify the way to appoint the board، its functions and competence، to establish an independent management of the board members; and the independence of the internal auditor and qualified him to perform his qualifying him duties in internal controls.